Following Spinoza: Knowledge as an Active State of Mind and a Motivator of Learning—An Empirically-Grounded Philosophical Study - Mounitz, Abraham (Journal of Ecohumanism, 2025)
Following Spinoza’s Ethics, the study seeks to provide an empirical corroboration for the hypothesis that the positive sensation associated with the acquisition of knowledge alongside the self-awareness of this sensation is the motivator for the acquisition of further knowledge. To this end, the study will present a theoretical grounding in the Ethics as the premise underpinning its subsequent empirical discussion. The empirical part is based on a three-year examination of students taking a logic course at Zefat Academic College. The statistical analysis of this examination confirms the theoretical premises established by Spinoza more than 350 years ago.